Adult ADHD and comorbid anxiety and depressive disorders: a review of etiology and treatment - Xinyu Fu; Weige Wu; Weige Wu; Yuru Wu; Xiaofu Liu; Wanting Liang; Rongchuan Wu; Yun Li; Yun Li (Frontiers in Psychiatry)
ObjectiveADHD, or Attention-Deficit/Hyperactivity Disorder, is a neurodevelopmental disorder that is known for its high degree of heterogeneity. It often coexists with other psychiatric diseases, especially anxiety and depression. This article reviews recent studies to explore the etiology of comorbid anxiety and depressive disorders in adults with ADHD, analyzing the factors contributing to this elevated comorbidity rate from several perspectives. Additionally, we explore potential directions for future research in this field.Recent findingsADHD exhibits a high comorbidity rate with anxiety and depressive disorders, due to overlapping and interacting symptoms. Individuals with two or more comorbid conditions often experience increased disease burden, prolonged illness duration, and diminished treatment efficacy. The underlying causes of comorbid anxiety and depression in ADHD patients are highly complex and can be understood from multiple dimensions, including genetics, neurobiology, neurocognition, and neuroimaging. This complexity poses significant challenges for clinical diagnosis and treatment. Currently, the management of ADHD patients with concurrent depression or anxiety may involve pharmaceutical interventions combined with non-pharmacological strategies, including psychotherapy (e.g., cognitive-behavioral therapy, CBT) and digital therapeutics. For patients with comorbid illnesses, these intergrated approaches have demonstrated significant improvements in symptom relief and quality of life enhancement.SummaryADHD is a highly heterogeneous disorder with a significant comorbidity rate. Recent research has elucidated the pathogenetic mechanisms of ADHD comorbid with depression and anxiety disorders from multiple perspectives. To improve patient functioning, enhance their quality of life, and guide more effective treatments, Further studies are needed to investigate the underlying causes of these comorbid conditions.